Taribavirin: a potential alternative to ribavirin. (March 2009) - Poordad, Fred F; Chee, Grace
Pegylated interferon and ribavirin are currently the standard of care therapy for chronic hepatitis C. In the near future, protease inhibitors are likely to be part of a three-drug regimen with interferon and ribavirin. It is not yet clear if therapy duration will be shorter, but it appears that anemia will be more severe. Ribavirin has to date been proven indispensible as a member of the treatment regimen, despite the potentially dangerous side effect of anemia. Taribavirin (viramidine), a purine nucleoside analog, is a prodrug of ribavirin. In a Phase III registration trial, it failed to show adequate efficacy but did have significantly less anemia when compared with weight-adjusted ribavirin. The dosing of taribaivirin may have been the flaw of that study, and indeed interim results of a Phase IIb study currently underway appear to have better antiviral effects with weight-based dosing. Sustained viral response rates comparable to ribavirin in a larger prospective study will be needed to supplant the current regimen. However, even if taribavirin efficacy is slightly lower than ribavirin, but anemia rates are considerably lower, there may still be a role for taribaivirin in a triple regimen where a protease molecule will be the predominant antiviral agent.